2005
DOI: 10.1111/j.1939-165x.2005.tb00076.x
|View full text |Cite
|
Sign up to set email alerts
|

Multilobulated “flower” cells in a subcutaneous mass aspirate from a cat

Abstract: An 8-year-old intact male cat was presented with a subcutaneous mass in the region of the right jugular vein. Cytologic and histopathologic examinations revealed cells with multilobulated nuclei (flower cells). Immunochemistry using a panel of markers showed vimentin-positivity on cytologic specimens, and postive staining for CD79a and BLA36 on histologic specimens. The final diagnosis was lymphoma of B-cell origin. We have observed similar multilobulated cells in ascites fluid, thoracic fluid, and peripheral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
1
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Interestingly, cytology allowed us to identify multilobate cells with clover-leaf shaped nuclei, rarely described before, that led us to consider a plasmablastic differentiation of cells. Based on two recent case reports [19,23], a suspect B-cell lymphoma with plasmablastic differentiation vs. a CP was emitted. Unfortunately, the evidence of these cells seems to be not suggestive of one or the other disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, cytology allowed us to identify multilobate cells with clover-leaf shaped nuclei, rarely described before, that led us to consider a plasmablastic differentiation of cells. Based on two recent case reports [19,23], a suspect B-cell lymphoma with plasmablastic differentiation vs. a CP was emitted. Unfortunately, the evidence of these cells seems to be not suggestive of one or the other disease.…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, the evidence of these cells seems to be not suggestive of one or the other disease. Lee et al [19] describe similar cells as "flower cells" in a dog diagnosed with CP, whereas Fritz et al [23] found them in a cat with a final diagnosis of cutaneous B-cell lymphoma.…”
Section: Discussionmentioning
confidence: 99%
“…Variable and pleomorphic nuclear shapes including band‐shaped, lobulated, and variably segmented nuclei were suggestive of myelomonocytic differentiation. Multilobulated “flower” cells are reported in cats and dogs with cells of myelomonocytic and B‐lymphoid cell origin . Circulating neoplastic lymphocytes with indented, cerebriform nuclei can be seen rarely in dogs with epitheliotropic T‐cell lymphoma and Sézary syndrome.…”
Section: Discussionmentioning
confidence: 99%